Command and its discontents: Instabilities of institutional anytime algorithms on a Clausewitz landscape. (July 2022) - Wallace, Rodrick
It has long been understood that the inevitably time-constrained cognitive processes of command on a Clausewitz landscape of uncertainty and imprecision are subject to gross instabilities. Even very experienced, capable, and intelligent command teams lose wars. Using formal approaches from control and information theories, we show how failure to understand and recognize underlying structure and dynamics in organized conflict expresses itself as increased "noise, " eventually triggering strategic collapse, often in a highly punctuated manner